Cupcakes, cookies & pie, oh, my! - Tack, Karen; Richardson, Alan , 1956- (Houghton Mifflin Harcourt, 2012)
The "New York Times"-bestselling authors of "Hello, Cupcake!" and "What's New, Cupcake?" are back, applying their wacky imagination not just to cupcakes, but to cookies, pies, cakes, and much more